Aspirin for thromboprophylaxis in major orthopedic surgery: old drug, new tricks? - Lippi, Giuseppeli; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2018)
Major orthopedic surgery, mainly entailing hip fracture surgery, hip and knee arthroplasty, is associated with significant morbidity and mortality, which are especially attributable to the high risk of postoperative VTE. Such a considerable risk is mainly due to a procoagulant state sustained by several important mechanisms, including massive release of procoagulants from tissue and bone damage, blood vessel injury, reduced venous emptying, perioperative immobilization and cement polymerization, among others. The risk of VTE during and after major orthopedic surgery approximates 50-80% in patients with no thromboprophylaxis, and persists for up 3 to 6 months after surgery. The anticoagulant or antithrombotic armamentarium entails several anticoagulants such as heparin, coumarins, fondaparinux, and the recently developed DOACs inhibiting either activated factor Xa (i.e., rivaroxaban, apixaban, edoxaban) or thrombin (i.e., dabigatran), as well as aspirin, i.e., the oldest antiplatelet drug to be ever discovered and used in clinical practice. The current guidelines are not in complete agreement regarding the choice of the ideal thromboprophylaxis, since some consider aspirin, and some discourage it. Recent evidence seems to support the use of aspirin in selected situations and in selected protocols. Therefore, we believe that consideration should be made about increasing the use of this old but still effective drug for perioperative prophylaxis of VTE, especially in patients for whom the administration of DOACs may be challenging.